Profits, R&D and labour: Breaking the law of diminishing returns to labour - Sara Amoroso (European Commission, Joint Research Centre (JRC), 2015)
A basic assumption in the economic literature is the one of diminishing marginal returns to labour. However, theoretical studies on knowledge and labour specialization assume that an increase in the knowledge investment embodied in the human capital of workers raises the marginal product of labour. In this paper, we propose a structural approach to test the hypothesis of non-diminishing returns to labour for a panel data set of R&D investing companies, and we explore how the marginal returns to labour vary with their level of knowledge capital (R&D) intensity. Our econometric analysis provides a number of results. First, we find that more knowledge intensive firms have non-diminishing returns to labour, while less knowledge intensive companies exhibit diminishing returns. Second, independently from the knowledge capital intensity, returns to labour increase with size. Relatively smaller firms have diminishing returns, while larger companies have non-diminishing to increasing returns to labour. However, we show that more knowledge intensive firms can attain the threshold of non-diminishing returns faster than their counterparts.
Keywords: J24; L10; L25; O30; 330; size; specialization; profitability; profit function